Prenatal Exposure to Perfluoroalkyl Substances Associated With Increased Susceptibility to Liver Injury in Children. Issue 5 (19th October 2020) - Stratakis, Nikos; V. Conti, David; Jin, Ran; Margetaki, Katerina; Valvi, Damaskini; Siskos, Alexandros P.; Maitre, Léa; Garcia, Erika; Varo, Nerea; Zhao, Yinqi; Roumeliotaki, Theano; Vafeiadi, Marina; et al.
Abstract : Background and Aims: Per‐ and polyfluoroalkyl substances (PFAS) are widespread and persistent pollutants that have been shown to have hepatotoxic effects in animal models. However, human evidence is scarce. We evaluated how prenatal exposure to PFAS associates with established serum biomarkers of liver injury and alterations in serum metabolome in children. Approach and Results: We used data from 1, 105 mothers and their children (median age, 8.2 years; interquartile range, 6.6‐9.1) from the European Human Early‐Life Exposome cohort (consisting of six existing population‐based birth cohorts in France, Greece, Lithuania, Norway, Spain, and the United Kingdom). We measured concentrations of perfluorooctane sulfonate, perfluorooctanoate, perfluorononanoate, perfluorohexane sulfonate, and perfluoroundecanoate in maternal blood. We assessed concentrations of alanine aminotransferase, aspartate aminotransferase, and gamma‐glutamyltransferase in child serum. Using Bayesian kernel machine regression, we found that higher exposure to PFAS during pregnancy was associated with higher liver enzyme levels in children. We also measured child serum metabolomics through a targeted assay and found significant perturbations in amino acid and glycerophospholipid metabolism associated with prenatal PFAS. A latent variable analysis identified a profile of children at high risk of liver injury (odds ratio, 1.56; 95% confidence interval, 1.21‐1.92) that was characterized by high prenatal exposure to PFAS and increased serum levels of branched‐chain amino acids (valine, leucine, and isoleucine), aromatic amino acids (tryptophan and phenylalanine), and glycerophospholipids (phosphatidylcholine [PC] aa C36:1 and Lyso‐PC a C18:1). Conclusions: Developmental exposure to PFAS can contribute to pediatric liver injury.